The Urgency of Protection of Hand-Rolled Kretek as Handicraft Product of Geographical Indication of Kudus District - Toebagus Galang Windi pratama (Fiat Justisia: Jurnal Ilmu Hukum, 2017)
Hand-rolled Kretek Protection as a Handicraft Product of Geographical Indication is an urgency because even though this product has taken r deep roots in Indonesian’s Culture, but because of the negative stigma of the danger of Cigarette made this product existence decreased over time, causing many small Hand-Kretek industries bankrupt and many Kretek-Roller Labourer Fired. The Study of Hand-Rolled Kretek as a Handicraft Product of Geographical Indication of Kudus District uses a Sociological Approach Method with Juridical-Empirical research method. The Primary data used in this research are Data Obtained from related people or Institution with the help of relevant literature, Documents and comparison to similar regulation from other countries as a secondary Data to find out whether Hand-Rolled Kretek is in accordance with product law provisions that can be a Geographical Indication Product of Handicraft or not and what implication that may occur. The result of the research shows that hand-rolled kretek can be a product of Geographical Indication because, regarding history, its distinguishing potential, and economic potential are sufficient, and are by the rules given, morality, religion and public order stated in Law No. 20 of 2016. The implications that arise can be seen both in the field of Economics such as increasing state income and employment, in the field of Social which can straighten the negative stigma of Hand-rolled kretek, and also in the field of Law where Hand-Rolled Kretek as a Geographical Indication Product of Handicraft can be used as a Reference for other industries to become a Geographical Indication products. Keyword: Hand-Rolled Kretek, Geographical Indication, Handicraft Product, Kudus District.